2006
DOI: 10.1080/j.1440-1665.2006.02269.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Attention Deficit Paradigm

Abstract: An alternative, more dimensional paradigm linking executive functions is described and its advantage over categorical diagnostic paradigms is argued. Consideration of a more discriminating and dimensional behavioural model would help psychiatrists operating in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Criticisms of a categorical DSM-IV diagnosis versus a dimensional approach to ADHD symptoms have been discussed elsewhere. 10 Omega-3 PUFA research adds an interesting insight to this debate. Most notably, three studies have found improvements in symptoms with a combined EPA and DHA supplement.…”
Section: Response To Commentarymentioning
confidence: 98%
“…Criticisms of a categorical DSM-IV diagnosis versus a dimensional approach to ADHD symptoms have been discussed elsewhere. 10 Omega-3 PUFA research adds an interesting insight to this debate. Most notably, three studies have found improvements in symptoms with a combined EPA and DHA supplement.…”
Section: Response To Commentarymentioning
confidence: 98%
“…Executive functions refer to problem solving skills, anticipation, strategic planning, self regulation, monitoring, maintenance of focus and task completion (Barkley 2000). Rosenman (2006) suggests that not all of the executive functions are impaired in ADHD; rather this differs across cases. Whitaker (2006) pinpoints the confusion around the definition of 'learning disability' (LD) in the literature.…”
Section: Introductionmentioning
confidence: 99%